THEOLOGICAL AND JURIDICAL PERSPECTIVES ON THE TEACHING OF AL-ISLAM AND MUHAMMADIYAH STUDIES (AIK) FOR NON-MUSLIM STUDENTS AT UNIVERSITAS MUHAMMADIYAH MATARAM - Palahuddin, Palahuddin; Wahab, Abdul; Hafiz, Abdul (Edukasi Islami: Jurnal Pendidikan Islam, 2024)
educational policies that accommodate the diverse religious backgrounds of students at Muhammadiyah Mataram University. Purpose: This study aims to determine how the theological and juridical perspective of the AIK learning policy for non-Muslim students at Muhammadiyah Mataram University (Ummat). There are 2 focuses of this research, namely how theological and juridical perspective of the AIK learning policy for non-Muslim students at Ummat.  Method: To achieve the intended goal, data collection is carried out using literature studies or literature. All data collected in this study will be analyzed using interactive analysis techniques proposed by Miles and Haberman which consists of three stages, namely: data reduction, data presentation, and conclusion. Result: The results of the research obtained information that in the theological review of the AIK learning policy for non-Muslim students is appropriate because they include ummat dakwah. Conclusion: Likewise, in the juridical perspective, this policy does not conflict with the applicable laws and regulations, because of 3 things, namely Ummat is an Educational Institution with Distinctive Religious Characteristics; they follow AIK learning willingly without any coercion; and AIK learning is used as a medium for intellectual processing and comparative material with the religion they profess